Comparison of Using One Trabecular Microbypass Stent versus Two during Cataract Surgery at Two Sites: One-Year Follow-Up. (7th April 2020) - Yang, Shuo; Ittarat, Mantapond; Tran, Elaine; Ferrell, Patricia; Wang, Gloria; Fisher, Ann C.; Li, Zhongqiu; Chang, Robert T.
Abstract : Purpose . To compare IOP and ocular hypotensive medication reduction of using one trabecular microbypass stent versus two in patients with open-angle glaucoma. Setting . Palo Alto Veterans Affairs (VA) Hospital and the Byers Eye Institute at Stanford University, Palo Alto, California, USA. Design . Retrospective case series. Methods . A chart review included patients who underwent trabecular microbypass implantation with cataract surgery in 2015-2017, with at least one-year follow-up. Subjects were divided into two groups by location (always one stent at Stanford versus two stents at the VA). Primary outcome measures included IOP and medication reduction at baseline and 12-month follow-up. Results . 132 subjects (166 eyes) were included. The preoperative IOP was 16.3 ± 3.4  mmHg on 2.6 ± 1.1 medications in the one-stent group (N = 85 ) and 17.5 ± 3.1  mmHg on 2.7 ± 0.6 medications in the two-stent group (N = 81 ). There was no significant difference between the two groups (p = 0.06 ). At the 12-month visit, there was a 13.37 % ± 2.93 reduction in IOP in the 1-stent group (p ≤ 0.001 ) and 13.49 % ± 2.69 in the 2-stent group (p ≤ 0.001 ); both were not significantly different from each other (p = 0.074 ). At 12 months, there was also a 14.5% reduction in medication use for the 1-stent group and 15.3% reduction in the 2-stent group, both statistically significant from baseline, (p = 0.022 and p = 0.037, respectively). Conclusions . Implantation with either one or two stents during cataract surgery in patients with glaucoma demonstrated similar IOP and med reduction in both groups between the two sites.